Africa's Growth Turnaround : From Fewer Mistakes to Sustained Growth - Page, John (World Bank, Washington, DC, 2017)
After stagnating for much of its postcolonial history, economic performance in Sub?Saharan Africa has markedly improved. Since 1995, average economic growth has been close to 5 percent per year. Has Africa finally turned the corner? This paper analyzes growth accelerations and decelerations-that is, country level deviations from long?run trend growth. Seen from this perspective, Africa's record of slow and volatile growth reflects a pattern of offsetting accelerations and declines, and much of the improvement in economic performance in Africa post 1995 turns out to be due to a substantial reduction in the frequency and severity of growth decelerations. The fall in economic declines since 1995 is largely due to better macroeconomic policies, but changes in such 'growth determinants' as investment, export diversification, and productivity have not accompanied the growth boom. Lack of change in these variables and the significant role played by natural resources in sparking growth accelerations suggest that Africa's growth recovery was fragile, even before the recent global economic crisis. The paper concludes by setting out four elements of a strategy that can help move Africa from fewer mistakes to sustained growth: managing natural resources better, pushing nontraditional exports, building the African private sector, and creating new skills.